2015
DOI: 10.5430/ijba.v6n3p72
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior towards Green Building: A Study in Abu Dhabi

Abstract: Green energy is a concept that has developed dramatically in recent years, for both professionals and regular consumers. One of the most important applications of green energy is 'Green Buildings'. This paper discusses Green Buildings from the perspective of the local consumers of Abu Dhabi city. Various elements of consumer preferences towards green buildings are evaluated in order to gauge their marketability in Abu Dhabi real estate market and the level of competition in the area. One of the research main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…That notwithstanding, scant work has been undertaken to systematically report upon what factors hold back the demand for GB among construction clients in extant literature. This study contributes to the discussion by seeking to argue thatthe solution to GB adoption is to have GB expansion driven by consumer demand rather than enforced rules and regulations (Abuamer and Boolaky, 2015). Consequently, it is imperative to bring into focus and conceptualize the market impediments of GB.…”
Section: Introductionmentioning
confidence: 99%
“…That notwithstanding, scant work has been undertaken to systematically report upon what factors hold back the demand for GB among construction clients in extant literature. This study contributes to the discussion by seeking to argue thatthe solution to GB adoption is to have GB expansion driven by consumer demand rather than enforced rules and regulations (Abuamer and Boolaky, 2015). Consequently, it is imperative to bring into focus and conceptualize the market impediments of GB.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the benefits offered by green buildings using GBTs, there is serious lag in the rate of its integration in constructions within developing countries. Although most developing countries have not taken the step of introducing regulatory or obligatory measures, Abuamer and Boolaky (2015) observed that GBTs do not advance by mere introduction of obligatory rules and regulations. According to Darko and Chan (2018), the GBT situation in developing countries requires radical steps for behavioural changes towards green concepts.…”
Section: S63mentioning
confidence: 99%
“…Under CVM, survey respondents are asked to express their WTP for different green features. According to Abuamer and Boolaky (2015), proliferating green construction will only be viable when the property is received positively by the end users. This requires increased awareness creation on the importance of green features in terms of cost saving and being eco-friendly.…”
Section: Abstract Energy Efficiency Green Features Submarketmentioning
confidence: 99%